2019
DOI: 10.4236/as.2019.101008
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic, Water Productivity and Economic Analysis of Irrigated Rice under Different Nitrogen and Water Management Methods

Abstract: The most limiting factors for irrigated rice farming are water and nitrogen. Efficient water and nitrogen management has remained critical for sustainable rice production in irrigated rice farming system. Due to rapid global population growth and climate change, future rice production will depend heavily on developing strategies and practices that use water and nitrogen efficiently. The study therefore set to evaluate agronomic, water productivity and economic analysis of irrigated rice under various nitrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
2
6
2
Order By: Relevance
“…The weights ranged from 24.6 to 30.8 as shown in Table 9. This is contrary to the findings of Yakubu [64], who reported that 1000-grain weight was not significantly (p > 0.05) influenced by N fertilizer and water management, as well as their interaction. However, these results conform to those of Yakubu [64] under interaction, in which there was no significant difference.…”
Section: Effect Of Water Management Nitrogen Levels and Their Interaction On Yield Characteristics Of Ricecontrasting
confidence: 99%
See 3 more Smart Citations
“…The weights ranged from 24.6 to 30.8 as shown in Table 9. This is contrary to the findings of Yakubu [64], who reported that 1000-grain weight was not significantly (p > 0.05) influenced by N fertilizer and water management, as well as their interaction. However, these results conform to those of Yakubu [64] under interaction, in which there was no significant difference.…”
Section: Effect Of Water Management Nitrogen Levels and Their Interaction On Yield Characteristics Of Ricecontrasting
confidence: 99%
“…This is contrary to the findings of Yakubu [64], who reported that 1000-grain weight was not significantly (p > 0.05) influenced by N fertilizer and water management, as well as their interaction. However, these results conform to those of Yakubu [64] under interaction, in which there was no significant difference. Straw yield; water management, nitrogen levels, and the interactions had a significant effect on straw yield.…”
Section: Effect Of Water Management Nitrogen Levels and Their Interaction On Yield Characteristics Of Ricecontrasting
confidence: 99%
See 2 more Smart Citations
“…Similar results were reported by Mazumder et al, 2019; Chen et al (2013) that nitrogen fertilization has a tendency to increase plant height as nitrogen involves cell division and cell elongation of plants. These results are in agreement with Yakubu et al, 2019, who reported increase of plant height under AWD water management and 90 kg N ha -1 nitrogen level. Zheng et al 2020 reported the contradicting results showing that the final plant height was significantly higher under flooding irrigation than that under water-saving irrigation treatments during both years of experiments.…”
Section: Trial With Lowland Soilsupporting
confidence: 93%